Spectral-Luminescent Properties of Titanium-Manganese Oxides - L.L.В Fedorenko; V.S.В Kshnyakin (Журнал нано- та електронної фізики)
We studied the photoluminescence (PL) of titanium-manganese mixed oxides TiO2/MnOx (TMO) obtained by chemical precipitation of manganese hydroxide on particles of rutile followed by annealing at different temperatures. It is found that the PL spectra, which were observed in the range 2.4В Г·В 3.4В eV, depend essentially on the phase composition of TMO. The blue shift of PL with decreasing nanocrystallite dimensions is related to the quantum-size effect. The PL quenching is due to the effect of oxygen vacancies and nonradiative Auger recombination. At low concentration of Mn (2В Г·В 9 at%), the PL efficiency increases due to the additional centers of recombination, but with increasing Mn level above the critical value (~В 13В at%) the efficiency falls down due to the effect of concentration quenching.